(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
The issue involving minorities and vulnerable groups has gained increasing prominence, especially in the aspects that comprise their guardianship. This is because, due to a multicultural and increasingly plural world, concerns about identities that become increasingly heterogeneous have been growing. In this universe, one of the great challenges encountered is the definition of the terms in question, since they are commonly used as synonyms, without being synonymous. The objective is to synthesize questions about Minorities, mediating historical information in the process of using the term, and to elucidate the importance of distinguishing the expression "minority" from the expression "vulnerable group", considering the existence of a scenario of doctrinal divergences about the very concept of minority, in which little has been done to indicate a special set of rights intended to ensure their inclusion in society and, consequently, the full exercise of citizenship. It is concluded that differentiating the terms can help in the realization of the rights of groups prevented from exercising their rights and groups that do not have these rights recognized. The study used the hypothetical-deductive method, according to the bibliographic and documentary procedures, respectively, through doctrines, scientific articles and international diplomas that exhibit the subject.